LC/ TOF/ ESI/ MS based detection of bioactive compounds present in leaf and bark extract of Acacia arabica - Biswas, Deboshree; Roymon, M G (Recent Research in Science and Technology, 2013)
An HPLC / MS/MS was employed to investigate bioactive principles present in methanolic leaf and bark extracts of Acacia arabica . The compounds commonly present in leaf and bark extracts were Oleic acid (C18H34O2), Myristic acid (C14H28O2), Palmitic acid (C16H32O2), Ferulic acid (C10H10O4), p-Coumaroyl-glucoside (C15H19O7), p -Coumaroylquinic acid (C16H18O8), Quercetine 3-O- (4’-O-acetyl)-rhamnopyranoside (C28H30O16) and Steroidal sapogenin. The other compounds observed in leaf extract were Caffeic acid phenethyl ester (CAPE) (C17H16O4), Epi catecine-3-gallate (C22H18O10) and Methyl 3,4,5 tri hydroxyl benzoate (C8H8O5). One compound seperately identified from bark extract was 3, 4, 5-trihydroxybenzoate (C7H6O5).